Relationship Stress Level and Leprosy Reactions in Leprosy Patients at Pondoh Indramayu Health Center - Purnamasari, Rina; Yasmin, Irma; Rahmah, Putri Dwi Septiani Luthfia (Nusantara Science and Technology Proceedings, 2024)
Leprosy is defined as a chronic progressive granuloma disease caused by Mycobacterium leprae (M.Leprae) that affects the peripheral nerves and skin. Leprosy reactions occur in leprosy patients before, during, and after leprosy treatment. One of the causes is stress. Stress can cause changes in immune responses that lead to leprosy reactions. The purpose of this research was to find out the relationship stress level and leprosy reactions in leprosy patients at Pondoh Indramayu Health Center. This research used an observational quantitative with cross sectional method. The sample in this research includes 49 leprosy reaction patients at the Pondoh Indramayu Health Center. Samples were taken by consecutive sampling methods based on inclusion criteria. The research period was November-December 2023 and the data were processed with the gamma correlation test. From the results of the gamma correlation test, there is a significant relationship between stress levels and leprosy reactions in leprosy patients at the Pondoh Indramayu Health Center.